Effect of couple's schema therapy in decreasing couples' tendency to divorce among divorce-applicant couples - Rahman Berdi Ozouni-Davaji; Kioumars Farahbakhsh; Masoumeh Esmaeily; Farangis Kazemi (Gonabad University of Medical Sciences, 2018)
The current study aimed to survey the effect of couple's schema therapy in reducing the tendency to divorce among divorce applicant couples. An experimental study was carried out in the form of single-subject design. The population study consisted of self-referential or referring couples to counseling centers as well as the counseling center of justice department. Three couples (wife and husband) were selected using purposive sampling method. Couple's schema therapy was conducted during 20 sessions with two-month follow-up. To collect data, demographic checklist and Rusbult tendency to divorce questionnaire were used. Data were analyzed using visual analysis, improvement percentage, reliable change index, and Cohen index. The findings showed that couple's schema therapy decreased tendency to divorce among divorcing couples and this reduction was clinically meaningful and statistically reliable (Reliable Change Index, RCI>1.96), The reduction in the tendency to divorce remained after two months and changes were clinically meaningful and statistically reliable (RCI>1.96), indicating the efficacy of couple's schema therapy in decreasing the tendency to divorce among couples